2017
DOI: 10.2514/1.b36510
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hard Start for Nontoxic Hypergolic Thruster Using H2O2 Oxidizer

Abstract: The present paper describes the phenomenon of hard start observed from a demonstrator of 500 N scale nontoxic hypergolic thruster using high-test peroxide as an oxidizer. When 90% concentration of hydrogen peroxide was used, the hard start was observed even under the fuel lead operation. To effectively suppress the occurrence of hard start phenomena in the startup phase of the thruster, oxidizer-to-fuel mass ratio and concentration of hydrogen peroxide have been individually considered. In drop tests, the igni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Handling of pure hydrides is challenging, because of their high reactive sensitivity to air and moisture (Sippel, et al 2011). Groups in Korea (Kang, Lee and Kwon 2017), Poland (Florczuk and Rarata 2017) In literature, it has been reported that some ILs are hypergolic with different oxidizers like white fuming nitic acid (WFNA), red fuming nitric acid (RFNA), NTO and HP (Sebastiano, et al 2014) (Zhang and Shreeve 2014). Very low ignition delay times for WFNA have been reported in the order of 1 ms (Zhang, et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Handling of pure hydrides is challenging, because of their high reactive sensitivity to air and moisture (Sippel, et al 2011). Groups in Korea (Kang, Lee and Kwon 2017), Poland (Florczuk and Rarata 2017) In literature, it has been reported that some ILs are hypergolic with different oxidizers like white fuming nitic acid (WFNA), red fuming nitric acid (RFNA), NTO and HP (Sebastiano, et al 2014) (Zhang and Shreeve 2014). Very low ignition delay times for WFNA have been reported in the order of 1 ms (Zhang, et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kang et al reported that a new bipropellant coupled with 98% H 2 O 2 delivers higher thrust than a combination of hydrazine and N 2 O 4 . 18 The contacts of H 2 O 2 with various fuels, such as alcohols, ketones, hydrocarbons, kerosene, and ionic liquids, are beneficial to develop hypergolic propellant formulations. 12,19−22 With respect to fuels, Al is the most popular due to its favorable properties, such as high energy density (30.5 kJ/g), wide availability, low cost, and environmentally benign products.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These catalysts include metallic Ag, Pt/Al 2 O 3 , Ir/Al 2 O 3 , MnO x /TiO 2 , and MnO x /ZrO 2 . The reaction of H 2 O 2 with a fuel can also generate a high specific impulse, functioning as a bipropellant. For example, Kang et al reported that a new bipropellant coupled with 98% H 2 O 2 delivers higher thrust than a combination of hydrazine and N 2 O 4 . The contacts of H 2 O 2 with various fuels, such as alcohols, ketones, hydrocarbons, kerosene, and ionic liquids, are beneficial to develop hypergolic propellant formulations. , …”
Section: Introductionmentioning
confidence: 99%
“…The schematic of the drop test stand is presented in Fig. 1 [9]. The procedure for this experiment is simple: a droplet of an oxidizer is released from a syringe or pipette; it falls down into the pool of a propellant stored in a vessel, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1. Schematic drawing of the drop test stand [9] The drop test allows the exploration of the variations of ignition delay under two extreme operating conditions: extreme fuel-rich combustion (oxidizer released as a droplet, fuel in the pool); or extreme oxidizer-rich combustion (fuel released as a droplet, oxidizer in the pool). The whole process is recorded by a high-speed camera.…”
Section: Introductionmentioning
confidence: 99%